(untitled) (Proceedings of the International Conference on Future of Women, 2018)
The paper presents a piece of a PhD research project about the evolution of the armed conflict axis conflict within the equality policies of the national government of Colombia, from 1992 to 2018. One of the hypothesis that orientates the research is that equality and gender equity policies have lower status in comparison to other public policies, such as peace. The low status is reflected in the lack of resources destined to building up a strong public institution in charge of promoting women’s rights, which could develop cross gender equality programs along with other ministries and public departments. It also focuses on the importance of the international law framework, such as the Beijing Platform and the United Nations Security Council resolutions on women, security and peace. Equality policies in Colombia have had an inconstant evolution. The public institution created for promoting them has been degrading in status, losing decision power and funding. The peace process has not always entailed the strengthening of public equality policies. On the contrary, in some legislations willing to promote peace agreements, equality policies have got no specific budget. Peace and equality are the two principles that governments have not built parallel. In addition, the gender mainstreaming approach in public policy has served to justify the lack of specific funding for the national institution responsible for promoting equality in the country and for the policies drafted.